Beginner's Communication Games - Hadfield, Jill (England Longman, 2009)
Beginner's communication games is a collection of 40 games for beginning students of english. It offers a photocopiable material , teacher's notes , photocopiable pictorial rules sheets to guide students.
Contents.
Keywords: Learning; Teaching; English - foreign language; Language